THE JUDICIAL IMPLEMENTATION OF THE RIGHT TO THE TRUTH: SOME THOUGHTS ON THE ARGENTINIAN EXPERIENCE OF THE JUICIOS POR LA VERDAD: Some thoughts on the Argentinian experience of the Juicios por la Verdad. - Chisari, Chiara (Pravni zapisi, 2022)
Safeguarding the right to the truth has become crucial in dealing with systematic violations of human rights. Especially in contexts of transition to democracy, telling the truth is considered of utmost importance for fighting against impunity and promoting peace. Nevertheless, scholars have paid little attention to the judicial implementation of this right and, in particular, to the value of judicial protection of the right to the truth. The article aims to fill this gap by discussing the Juicios por la Verdad (the Truth Trials), a unique experience promoted by the Argentinian civil society in the wake of the military dictatorship. Specifically, it investigates the impact of the judicial recognition of the right to the truth on both the victims’ lives and society’s attempt to come to terms with the past. The analysis shows that the right to the truth may serve as a tool for knowledge, acknowledgment, strengthening the rule of law and, to an extent, for justice.
Keywords: right to the truth; judicial implementation; value of the judicial truth; Juicios por la Verdad; the Truth Trials; Argentina; transitional justice